2005
DOI: 10.1055/s-2005-918963
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinite Thioglycosides Derived from Natural d-Sugars as Useful P/S Ligands for the Synthesis of Both Enantiomers in Palladium-Catalyzed Asymmetric Substitution

Abstract: Phosphinite thioglycosides I for which a modular synthetic approach is reported, were found highly efficient catalyst precursors for palladium(0)-catalyzed asymmetric substitution. Both enantiomers of the allylated products have been obtained with high ee (up to 96%) using natural sugars as catalyst precursors.Key words: P/S ligands, carbohydrates, both enantiomers, allylic substitutionThe difficulty to predict the structural requirements of a ligand for acting as a successful catalyst explains the enduring ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 7 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…We have recently found that in the case of sterically hindered tert-butanethiol the thioglycosilation takes place under thermodynamic control, being the α-thioglycoside the more stable isomer. 22 Similarly, and in order to obtain the kinetic isomer, the reaction was conducted at 0ºC affording the desired product 4 in 70% yield as a white solid.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently found that in the case of sterically hindered tert-butanethiol the thioglycosilation takes place under thermodynamic control, being the α-thioglycoside the more stable isomer. 22 Similarly, and in order to obtain the kinetic isomer, the reaction was conducted at 0ºC affording the desired product 4 in 70% yield as a white solid.…”
Section: Resultsmentioning
confidence: 99%
“…22 This stereocontrol coupled with the higher trans effect of phosphorus vs. sulfur 23 led to the discovery, of ligands 1 and 2 derived from D-sugars galactose and arabinose as excellent catalyst precursors for the synthesis of L-and D-amino esters, Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…[a] 20 D : +13. 9 (c. 0.6,CHCl 3 (d,J ¼ 18.3 Hz),129.4 (d,J ¼ 51.4 Hz),128.7,128.6,128.5,128.4,128.3,128.2,126.1,101.8 (CHPh) (11).…”
Section: General Procedures Of the Opening Epoxide Reactionmentioning
confidence: 99%
“… 36 Interestingly, ligation of 28 to a Pd-centre afforded selectively a single diastereomer, resulting from preferential coordination of one of the two diastereotopic sulfur lone pairs. 36 , 37 This system was evaluated in Pd-catalysed AAA of dimethylmalonate with ( E )-1,3-diphenylallyl acetate ( 29 ) and gave 30 in high yield and 92% ee. The synthesis of a pseudo-enantiomeric version of 28 , where a d -arabinose core was used to invert the stereo-relationship between the S and P groups, was also described.…”
Section: Selected Examplesmentioning
confidence: 99%
“…The synthesis of a pseudo-enantiomeric version of 28 , where a d -arabinose core was used to invert the stereo-relationship between the S and P groups, was also described. 36 Both systems were also evaluated in asymmetric Rh-catalysed hydrogenations of enamides.…”
Section: Selected Examplesmentioning
confidence: 99%